Determining the biological effects of functional amino acid supplementation in low crude protein diet on growth performance of broiler chicken - Shazali, Nurhazirah; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Saad, Wan Zuhainis; Mohamad, Rosfarizan; Abdul Rahim, Raha (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
This experiment was conducted to determine the biological effect of functional amino acid supplementation in low crude protein diet on growth performance of broiler chicken. A total of 288 male Cobb 500 chicks were allocated into 8 treatment groups and were fed with essential amino acids supplementation in low crude protein diet. Diets contain 21% crude protein until 18% crude protein and supplemented with amino acid (L- lysine, DL-methionine and L-threonine). This experiment was conducted for 6 weeks and the feed intake, body weight, feed conversion ratio were measured weekly. There was no significant different (P>0.05) in feed intake among the treatment groups. The reducing level of crude protein from 21% until 18% supplemented with amino acid (T2-T8) was significantly (P<0.05) higher in body weight (WG), average daily gain (ADG) and total weight gain (TWG) as compared with T1. Overall result shows 19% crude protein contained optimum level of amino acidshad better BW, ADG, FI and lower FCR. Thus, with this reduction of crude protein it will reduce the production costs concurrently maintain the broiler performance.